Cost Management Strategy: Application of Activity Based Costing Method to Optimize Cost Prices - Indrayani, Rina; Koesindratmono, Ferry; Suwarman, Herman Ruswan; Yunita, Nia (Enrichment : Journal of Management, 2025)
A shoe manufacturer is struggling with high COGS, making it less competitive due to inaccurate cost allocation from traditional pricing methods. This study explores the Activity-Based Costing (ABC) method as a more precise approach to assigning costs based on actual activities and resource usage. Comparing both methods, traditional costs for flat shoes and heels are IDR 64,195 and IDR 100,545, while ABC calculations show lower costs of IDR 62,958 and IDR 98,700—resulting in savings of IDR 1,237 and IDR 1,845. These findings highlight how ABC improves cost accuracy, enhances efficiency, and supports a more competitive pricing strategy. Additionally, it helps identify non-value-added activities, ultimately boosting profitability and strengthening the company’s position in the footwear industry.